Intrathecal Oxytocin Improves Spontaneous Behavior and Reduces Mechanical Hypersensitivity in a Rat Model of Postoperative Pain - Espinosa De Los Monteros-Zúñiga, Antonio; Martínez-Lorenzana, Guadalupe; Condés-Lara, Miguel; González-Hernández, Abimael (Frontiers in Pharmacology, 2020)
The first few days post-surgery, patients experience intense pain, hypersensitivity and consequently tend to have minor locomotor activity to avoid pain. Certainly, injury to peripheral tissues produces pain and increases sensitivity to painful (hyperalgesia) and non-painful (allodynia) stimuli. In this regard, preemptive pharmacological treatments to avoid or diminish pain after surgery are relevant. Recent data suggest that the neuropeptide oxytocin when given at spinal cord level could be a molecule with potential preemptive analgesic effects, but this hypothesis has not been properly tested. Using a validated postoperative pain model (i.e. plantar incision), we evaluated in male Wistar rats the potential preemptive antinociceptive effects of intrathecal oxytocin administration measuring tactile hypersensitivity (across eight days) and spontaneous motor activity (across three days). Hypersensitivity was evaluated using von Frey filaments, whereas spontaneous activity (total distance, vertical activity episodes, and time spent in the center of the box) was assessed in real time using a semiautomated open-field system. Under these conditions, we found that animals pretreated with spinal oxytocin before plantar incision showed a diminution of hypersensitivity and an improvement of spontaneous behavior (particularly total distance and vertical activity episodes). This report provides a basis for addressing the therapeutic relevance of oxytocin as a potential preemptive analgesic molecule.